Safety stressors, safety-specific trust, and safety citizenship behavior: A contingency perspective - Wang, D.; Wang, X.; Griffin, Mark; Wang, Z. (2020)
Employee safety citizenship behavior (SCB) is critical for workplace safety in a high-risk work environment, but few studies have addressed how safety stressors affect SCB. This study investigates the different relationships between safety stressors (safety role ambiguity, safety role conflict, and interpersonal safety conflict) and two forms of SCB (proactive and prosocial). It also examines the moderating effect of safety-specific trust (cognition- and affect-based) within these relationships. An analysis of 332 multisource data from frontline workers and their safety supervisors in China reveals that safety role ambiguity and safety role conflict negatively affect proactive safety behaviors, while interpersonal safety conflict impedes prosocial safety behaviors. Additionally, cognition-based safety trust alleviates the effects of safety role ambiguity and safety role conflict on proactive safety behaviors, whereas affect-based safety trust effectively restricts the influence of interpersonal safety conflict on prosocial safety behaviors. These results suggest that managers need to instill SCB in their subordinates and combat stressful conditions through interventions that enhance safety-specific trust.